PENGARUH KARAKTERISTIK INDIVIDU TERHADAP PRESTASI KERJA MELALUI DISIPLIN KERJA DAN KEPUASAN KERJA - Riyanto; Gunarso Wiwoho (Universitas Ahmad Dahlan, 2022)
This research was conducted to analyze the effect of individual characteristics on work performance with work discipline and job satisfaction as intervention variables. The population of this research was employees at PT Prima Multi Usaha Indonesia with 34 people as sample. The retrieval technique for the sample is saturated sampling. The research instrument of this study was a survey questionnaire which was measured on a 5-level Likert scale. The data obtained were processed by SPSS (Statistical Product and Service Solution) for Windows version 24.0 to run the descriptive analysis and statistical analysis (path analysis). The results showed that there was a positive effect between individual characteristics on job satisfaction, individual characteristics have a positive effect on work discipline, individual characteristics have a positive effect but not significant to work performance, job satisfaction has a positive effect on work performance, and work discipline has a positive effect on work performance.